Open Pelvic Fractures: Review of 30 Cases - Giordano, Vincenzo (Open Orthop J, 2016)
BACKGROUND: Open pelvic fractures are rare but usually associated with a high incidence of complications and increased mortality rates. The aim of this study was to retrospectively evaluate all consecutive open pelvic fractures in patients treated at a single Level-1 Trauma Center during a 10-year interval. PATIENTS AND METHODS: In a 10-year interval, 30 patients with a diagnosis of open pelvic fracture were admitted at a Level-1 Trauma Center. A retrospective analysis was conducted on data obtained from the medical records, which included patient’s age, sex, mechanism of injury, classification of the pelvic lesion, Injury Severity Score (ISS), emergency interventions, surgical interventions, length of hospital and Intensive Care Unit stay, and complications, including perioperative complications and death. The Jones classification was used to characterize the energy of the pelvic trauma and the Faringer classification to define the location of the open wound. Among the survivors, the results were assessed in the last outpatient visit using the EuroQol EQ-5D and the Blake questionnaires. It was established the relationship between the mortality and morbidity and these classification systems by using the Mann-Whitney non-parametric test, with a level of significance of 5%. RESULTS: Twelve (40%) patients died either from the pelvic lesion or related injuries. All of them had an ISS superior to 35. The Jones classification showed a direct relationship to the mortality rate in those patients (p = 0.012). In the 18 (60%) other patients evaluated, the mean follow-up was 16.3 months, ranging from 24 to 112 months. Eleven (61%) patients had a satisfactory outcome. The Jones classification showed a statistically significant relationship both to the objective and subjective outcomes (p < 5%). The Faringer classification showed a statistically significant relationship to the subjective, but not to the objective outcome. In addition, among the 18 patients evaluated at the last outpatient visit, the Faringer classification showed statistical significance on the need of colostomy (p = 0.001) in the acute phase of treatment. CONCLUSION: We suggest the routine use of the Jones classification for the emergency room assessment and management of all open fractures of the pelvic ring. We believe the Faringer classification seems to be useful for the abdominal surgeons for the indication of gut transit derivation but not for the acute management of the bony component of an open pelvic fracture.